Garden pests - Abdukarimova Mamlakat Abdukarimovna; Kulmurotova Aziza Muhiddinovna (Zien Journals, 2023)
This paper provides information on the control of sucking pests in intensive fruit orchards by studying the bioecology of sucking pests such as aphids, aphids, spider mites, scale insects, mealybugs, etc.
Keywords: Pesticide; joint; entomophagus; imoga